1998
DOI: 10.1017/s0885715600009994
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic studies of BaR2ZnO5 (R=La, Nd, Dy, Ho, Er, and Y)

Abstract: The crystal structures of BaR 2 Zn0 5 , where R=La, Nd, Dy, Ho, and Y, were studied by neutron diffraction, and that of the Er analog was investigated by synchrotron X-ray diffraction. Two structure types were confirmed for this series of compounds and agreed with those reported in literature. The compounds with a smaller size of R (R=Dy, Ho, Y, and Er) are isostructural to the orthorhombic "green phase (BaY 2 CuO 5 )" compounds. The cell parameters for compounds with the R=Er to Dy range from a = 7.0472(1) A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…The refined structural parameters show good agreement with the previous structural studies [17,22] and in particular the significant decrease in cell constants and cell volume linked to the replacement of lanthanum by neodymium is clear. The effect of partially replacing the lanthanides by Ca 2+ on the lattice parameters of the samples is shown in Fig.…”
Section: Crystal Structuresupporting
confidence: 86%
See 1 more Smart Citation
“…The refined structural parameters show good agreement with the previous structural studies [17,22] and in particular the significant decrease in cell constants and cell volume linked to the replacement of lanthanum by neodymium is clear. The effect of partially replacing the lanthanides by Ca 2+ on the lattice parameters of the samples is shown in Fig.…”
Section: Crystal Structuresupporting
confidence: 86%
“…AC conductivity (10 kHz) measurements were performed with a Solartron 1260 FRA as a function of the oxygen partial pressure between values corresponding to wet hydrogen and wet oxygen, and as a function of the water vapour partial pressure from dry (3 × 10 −5 atm) to wet (0.028 atm) conditions in the temperature range of 400 to 1000°C. Rietveld analysis of the long scan data sets recorded for x = 0, 0.05, 0.1 and 0.15 samples was undertaken using the basic starting model suggested by Michel et al [17] and subsequently confirmed by WongNg et al [22] based on analysis of neutron diffraction data. This has distinct positions for the lanthanide and barium ions within the tetragonal unit cell.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Successful replacement of Cu by Zn in the lanthanide Ba-R-Cu-O system has been described [59]. According to Michel et al [58], selected barium lanthanum zinc oxides apparently isostructural to the “green phases”, BaR 2 CuO 5 [2], can be prepared.…”
Section: Introductionmentioning
confidence: 99%
“…According to Michel et al [58], selected barium lanthanum zinc oxides apparently isostructural to the “green phases”, BaR 2 CuO 5 [2], can be prepared. The structures of the La, Nd, and Y-compounds have been studied using x-ray powder diffraction [5,6] and neutron powder diffraction methods [9]. It was found that, while the structures of the La and Nd analogs are tetragonal, the Y-compound is orthorhombic.…”
Section: Introductionmentioning
confidence: 99%
“…1 hain of one-cap trigonal prisms (6,5,0) and ( Layer of trigonal dodecahedra (7,5,0) and pentagonal bipyramids ( 3 Framework of one-cap trigonal prisms (7,9,2), (6,5,0), (6,5,0) and (4, 3, (8,7,1), pentagonal bipyramids (7,5,1) and (7,5,0) and octahedra (5, 2, (8,6, 0), (8, 6, 0), (8,5, 0) and (7,5,1) and pentagonal bipyramids (7, 5, 3 Framework of trigonal dodecahedra (8,12,0) and pentagonal bipyramids (7, 9, 3 Framework of pentagonal bipyramids (7, 11, 1), (7, 10, 1) and octahedra (6, 9, atoms, varies from 0.085 to 0.079. With an increase in the C.N., the G 3 value decreases, indicating an increase in the environment uniformity.…”
mentioning
confidence: 99%